Time-Course Global Expression Profiles of Chlamydomonas reinhardtii during Photo-Biological H(2) Production - Nguyen, Anh Vu (Public Library of Science, 2011)
We used a microarray study in order to compare the time course expression profiles of two Chlamydomonas reinhardtii strains, namely the high H(2) producing mutant stm6glc4 and its parental WT strain during H(2) production induced by sulfur starvation. Major cellular reorganizations in photosynthetic apparatus, sulfur and carbon metabolism upon H(2) production were confirmed as common to both strains. More importantly, our results pointed out factors which lead to the higher H(2) production in the mutant including a higher starch accumulation in the aerobic phase and a lower competition between the H(2)ase pathway and alternative electron sinks within the H(2) production phase. Key candidate genes of interest with differential expression pattern include LHCSR3, essential for efficient energy quenching (qE). The reduced LHCSR3 protein expression in mutant stm6glc4 could be closely related to the high-light sensitive phenotype. H(2) measurements carried out with the LHCSR3 knock-out mutant npq4 however clearly demonstrated that a complete loss of this protein has almost no impact on H(2) yields under moderate light conditions. The nuclear gene disrupted in the high H(2) producing mutant stm6glc4 encodes for the mitochondrial transcription termination factor (mTERF) MOC1, whose expression strongly increases during –S-induced H(2) production in WT strains. Studies under phototrophic high-light conditions demonstrated that the presence of functional MOC1 is a prerequisite for proper LHCSR3 expression. Furthermore knock-down of MOC1 in a WT strain was shown to improve the total H(2) yield significantly suggesting that this strategy could be applied to further enhance H(2) production in other strains already displaying a high H(2) production capacity. By combining our array data with previously published metabolomics data we can now explain some of the phenotypic characteristics which lead to an elevated H(2) production in stm6glc4.